Sistem Informasi Bursa Kerja Khusus SMK Negeri 1 Bendo Berbasis Web - Alfian Eka Felani; Joko Triono; Daniel Wahyu Suprayoga Prabowo (LPPM Universitas Merdeka Madiun, 2022)
SMK Negeri 1 Bendo is a school engaged in industrial technology vocational education. The special job market for SMK Negeri 1 Bendo is tasked with channeling alumni to the business world and the industrial world, currently the distribution of job exchanges is carried out with whatsapp groups which are considered less effective and the application process for the administrative stage is still conventional. Manual documentation is not only troublesome in making reports, it also makes it difficult to search for data. To overcome these problems, The Job Market Information System was created specifically for SMK Negeri 1 Bendo. The result of this research is a Job Market Information System specifically SMK Negeri 1 Bendo web-based. The system is made by waterfall development method and using Laravel framework. With this information system, it can help the distribution of job market information to alumni become more efficient.